The study of fibroblast proteome changes in the presence of Ethanol - Rezaei-Tavirani, Majid; Rezaei-Tavirani, Mostafa; Rahmati Rad, Sara; Zali, Hakimeh; Hasanzadeh, Hadi; Aminigram, Pooneh (Archives of Advances in Biosciences, 2014)
Ethanol known as ethyl alcohol is being widely used around the world. Many serious diseases are related with its consumption. Alcohol posses many divers effects on human body including risk of cirrhosis and/or hepatocellular carcinoma. Therefore, analysis of this component is prominent. Fibroblast cells were cultured in various dosages of ethanol. The effective dosage was then investigated by proteomic methods. Separated proteins of fibroblast cells by Two-Dimensional Gel (2DG) Electrophoresis method based on pI and MW were analyzed based on spots alteration by Same Spot Software. Furthered analysis was carried out with vigorous statistical analysis based on significant folding changes and one-way ANOVA. About 372 protein spots were identified and among them 65 of them were having significant expression profile, which is evaluated as p <0.05. Therefore, ethanol can induce a great impact on protein profile of fibroblast. It is concluded that altering morphologic features and viability, as well as protein expression changes, confirm toxic properties of ethanol in human body.